2018
DOI: 10.2139/ssrn.3152120
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practice of Drivers Towards Traffic Rules and Regulations in Multan, Pakistan

Abstract: Traffic rules are an important agenda for the developing countries and the situation has become worsened particularly in Pakistan. Most of the road accidents are resulting due to lack of knowledge, negative attitudes and risky practices of drivers towards traffic rules and regulations. To highlight the knowledge, attitude and practices of professional drivers towards traffic rules, this research work was initiated. The objective of research was to determine and explore the knowledge, attitudes and practice tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…But, the present finding revealed the statistical significant difference of drivers' attitude scales towards traf-fic regulations and its subsequent risk of RTC or sustained road traffic crash. This finding was also supported by studies of Riaz and Shahid [12] and Tajvar et al [13] who conducted study among drivers in Pakistan and Iran respectively. Additionally, Yahia et al [14] also reported there is no statistically significant gender difference among drivers' attitude towards RTS in regards to degree of RTC occurrence.…”
Section: Attitude Of Drivers Towards Traffic Regulationsupporting
confidence: 76%
“…But, the present finding revealed the statistical significant difference of drivers' attitude scales towards traf-fic regulations and its subsequent risk of RTC or sustained road traffic crash. This finding was also supported by studies of Riaz and Shahid [12] and Tajvar et al [13] who conducted study among drivers in Pakistan and Iran respectively. Additionally, Yahia et al [14] also reported there is no statistically significant gender difference among drivers' attitude towards RTS in regards to degree of RTC occurrence.…”
Section: Attitude Of Drivers Towards Traffic Regulationsupporting
confidence: 76%
“…The finding is inconsistent with another study conducted among motorists in Mangaluru suburbs (Shetty et al, 2017) which revealed that more than two-thirds (67.2%) had insufficient awareness about road traffic rules. Again, another study conducted in Multan, Pakistan (Riaz and Shahid, 2018) was contradictory to the findings of the researcher which revealed that the maximum number of professional drivers had inadequate knowledge about traffic sign boards (87.64%) and were less aware. The difference in results might be due to the difference in driving experience, literacy rate of the population or road safety education might not be a part of their school curriculum and the reduced exposure to IEC activities.…”
Section: Discussionmentioning
confidence: 65%
“…[ 6 ] In the present study, 46.9% of them knew that the right side of the road must be used to overtake the vehicle similar to a study done in Pakistan by Riaz and Shahid, where 47% of them thought that overtaking from left is not a good practice for the drivers. [ 7 ] About 97.7% of the study participants in the present study knew that it is mandatory to wear helmet while driving scooter/bike in India. In a study done by Siviroj et al ., about 55.8% of them were aware of danger of not using a helmet.…”
Section: Discussionmentioning
confidence: 92%